The Impact of Aspirin on Ultrasound Markers of Uteroplacental Flow in Low-Risk Pregnancy: Secondary Analysis of a Multicenter RCT - Mulcahy, Cecilia; Mone, Fionnuala; McParland, Peter; Breathnach, Fionnuala; Cody, Fiona; Morrison, John J.; Higgins, John; Daly, Sean; Dornan, Samina; Cotter, Amanda; Dicker, Patrick; Tully, Elizabeth; Malone, Fergal D.; McAuliffe, Fionnuala M. (American Journal of Perinatology, 2019)
Objective This article evaluates the effect of low-dose aspirin on uterine artery (UtA) Doppler, placental volume, and vascularization flow indices in low-risk pregnancy.Study Design In this secondary analysis of the TEST randomized controlled trial, low-risk nulliparous women were originally randomized at 11 weeks to: (1) routine aspirin 75 mg; (2) no aspirin; and (3) aspirin based upon the preeclampsia Fetal Medicine Foundation screening test. UtA Doppler, three-dimensional (3D) placental volume, and vascularization flow indices were assessed prior to and 6 weeks postaspirin commencement.Results A total of 546 women were included (aspirin n = 192, no aspirin n = 354). Between first and second trimesters, aspirin use was not associated with a change in UtA Doppler, placental volume, or vascular flow indices. There was no significant difference in the change in UtA Doppler pulsatility index (PI) Z-scores or notching (PI Z-score –0.2 vs. –0.2, p = 0.17), nor was there a significant change in placental volume Z-score and vascular flow indices (volume Z-score change: 0.74 vs. 0.62, p = 0.34).Conclusion Low-dose aspirin commenced at 11 weeks in low-risk women does not appear to improve uterine and placental perfusion or placental volume. Any perceived effect on uteroplacental vasculature is not reflected in changes in placental volume nor uteroplacental flow as assessed by two-dimensional and 3D ultrasound.
Keywords: aspirin; uteroplacental; uterine artery Doppler; placental volume; 3D ultrasound; three-dimensional power Doppler indices